Entering uncharted waters? ASEAN and the south china sea (Institute of Southeast Asian Studies, 2013)
ASEAN has an abiding interest in peace and stability in this region and in freedom of navigation in and overflight above the South China Sea. Much of ASEANs commerce, including its members' traded food and energy resources, passes through or over the South China Sea. The stakes for ASEAN and its members in the South China Sea are very high.This book is the product of a conference on Entering Uncharted Waters? ASEAN and the South China Sea Dispute, initiated to remind all claimants to bring their claims as close as possible to the provisions of the 1982 UN Convention on the Law of the Sea. After all, ASEAN has sought to promote the rule of law in the region.
Keywords: Territorial waters--South China Sea; Dispute resolution (Law)--Southeast Asia; Conflict management--Southeast Asia